2021
DOI: 10.1002/asia.202100793
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Molecular Mechanisms of Histone Code Recognition by the BRPF3 Bromodomain

Abstract: Bromodomains are evolutionarily conserved reader modules that recognize acetylated lysine residues on the histone tails to facilitate gene transcription. The bromodomain and PHD finger containing protein 3 (BRPF3) is a scaffolding protein that forms a tetrameric complex with HBO1 histone acetyltransferase (HAT) and two other subunits, which is known to regulate the HAT activity and substrate specificity. However, its molecular mechanism, histone ligands, and biological functions remain unknown. Herein, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…More recent studies on the family IV bromodomains revealed that BRPF1 recognizes H3K14ac and H2AK5ac ligands with a moderate affinity, and the BRPF3 and ATAD2/B forms transient interactions with the histone H2AK5ac ligand (34-36,38,39). We also tested the binding affinity of the BRPF2 bromodomain with histone peptides H3K14ac (9-19) and H2AK5ac (1-12).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…More recent studies on the family IV bromodomains revealed that BRPF1 recognizes H3K14ac and H2AK5ac ligands with a moderate affinity, and the BRPF3 and ATAD2/B forms transient interactions with the histone H2AK5ac ligand (34-36,38,39). We also tested the binding affinity of the BRPF2 bromodomain with histone peptides H3K14ac (9-19) and H2AK5ac (1-12).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not clear how BRPF2 directs the recruitment of HBO1 HAT to chromatin to regulate the gene transcription. Recent studies on the BRPF3 bromodomain demonstrate that it recognizes multiple acetylated lysine residues on the N-terminal tails of histone H4 and shows preferential interactions with H4K5ac and H4K5acK12ac marks (36). Since the sequence similarity between the BRPF2 and BRPF3 bromodomains is high, most likely, the BRPF2 bromodomain recognizes a similar set of acetylated histone modifications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations